Mobility of cytochrome P450 in the endoplasmic reticulum membrane - Szczesna-Skorupa, Elzbieta (The National Academy of Sciences, 1998)
Cytochrome P450 2C2 is a resident endoplasmic reticulum (ER) membrane protein that is excluded from the recycling pathway and contains redundant retention functions in its N-terminal transmembrane signal/anchor sequence and its large, cytoplasmic domain. Unlike some ER resident proteins, cytochrome P450 2C2 does not contain any known retention/retrieval signals. One hypothesis to explain exclusion of resident ER proteins from the transport pathway is the formation of networks by interaction with other proteins that immobilize the proteins and are incompatible with packaging into the transport vesicles. To determine the mobility of cytochrome P450 in the ER membrane, chimeric proteins of either cytochrome P450 2C2, its catalytic domain, or the cytochrome P450 2C1 N-terminal signal/anchor sequence fused to green fluorescent protein (GFP) were expressed in transiently transfected COS1 cells. The laurate hydroxylase activities of cytochrome P450 2C2 or the catalytic domain with GFP fused to the C terminus were similar to the native enzyme. The mobilities of the proteins in the membrane were determined by recovery of fluorescence after photobleaching. Diffusion coefficients for all P450 chimeras were similar, ranging from 2.6 to 6.2 × 10(−10) cm(2)/s. A coefficient only slightly larger (7.1 × 10(−10) cm(2)/s) was determined for a GFP chimera that contained a C-terminal dilysine ER retention signal and entered the recycling pathway. These data indicate that exclusion of cytochrome P450 from the recycling pathway is not mediated by immobilization in large protein complexes.